Detection and quantification of Salmonella spp. in poultry slaughterhouses of southern Brazil - Karen Apellanis Borges; Eduarda Boff Martelo; Lilian Andriva dos Santos; Thales Quedi Furian; Isabel C Cisco; Luciane Manto; Luciana R dos Santos (Journal of Infection in Developing Countries)
Introduction: Salmonella is a major cause of foodborne illness throughout the world. The use of quantitative techniques is important for assessing the risk and determining the capacity of each step of the slaughtering process to decrease or increase bacterial contamination. We aimed to detect and to quantify the presence of Salmonella in Brazilian processing plants by real-time quantitative polymerase chain reaction (qPCR).